Gods schepselen: Dieren in het licht van schepping, verlossing en voltooiing - Hausoul, R. R. (Theologia reformata, 2024)
In light of the increasing attention to animal welfare, this article examines the place of animals in Christian tradition and Biblical focus on creation, redemption, and consummation. The article argues that animals are integral to God's plan for all creation, and then briefly looks at the question whether animals in the new creation will be newly created, resurrected or immortal. The article shows that God's care extends to all living things and that animals have a place in God's plan of redemption. This points to the need for a renewed focus on animals within Christian theology.